2022
DOI: 10.1680/jgeot.20.p.259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curing conditions on the hydromechanical properties of a metakaolin-based soilcrete

Abstract: An attractive approach to reduce the carbon footprint of deep soil mixing (DSM) is to replace Portland cement-based binders by geopolymers based on metakaolin. Safe design requires a good understanding of the mechanical and hydraulic properties of the improved ground but very little is known about metakaolin-soil mixtures. For instance, shrinkage during curing is a significant issue for metakaolin-based concretes but has not been previously studied in soilcretes. In this work the permeability and strength of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…It has been reported that dry curing of pure CS results in even higher strength gains than wet curing (Axelsson 2006). On the other hand, dry curing of pure MK results in severe mechanical damage to the material (Spagnoli et al 2021a). This was borne out by our tests, where in dry-D r a f t cured CS treated specimens UCS systematically increased, whereas metakaolin treated specimens (SMK(100)D and SOMK(100)D) reduced strength and became more ductile during the curing period.…”
Section: Unconfined Compressive Strength (Ucs)mentioning
confidence: 64%
See 4 more Smart Citations
“…It has been reported that dry curing of pure CS results in even higher strength gains than wet curing (Axelsson 2006). On the other hand, dry curing of pure MK results in severe mechanical damage to the material (Spagnoli et al 2021a). This was borne out by our tests, where in dry-D r a f t cured CS treated specimens UCS systematically increased, whereas metakaolin treated specimens (SMK(100)D and SOMK(100)D) reduced strength and became more ductile during the curing period.…”
Section: Unconfined Compressive Strength (Ucs)mentioning
confidence: 64%
“…Contrary to what happened with UCS the effect of curing time on the triaxial response of dry-cured MK treated specimens was rather small, showing lesser or no clear decay of peak mobilised strength with time (Figure 8). This suggests that confinement inhibited the mechanical effect of MK micro-cracking that was visible on microscopic images (Spagnoli et al 2021a) Undrained secant Young moduli are presented in Figure 9 (at a small strain level) and Figure 10 (at intermediate strain levels). In these figures the strain level effect (decreasing stiffness as strain level increases) is larger than the stress level effect (stiffness increases as confinement increases).…”
Section: Monotonic Triaxial Undrained Compression (Txciu)mentioning
confidence: 94%
See 3 more Smart Citations